Behavior associated a pathology without the presence of disease: A study case - Winter Edgar Reyna Cruz; César Alberto Tapia Barrón; Cristian Javier Ocampo Solis; María de Lourdes Rodríguez Campuzano (Interacciones)
Introduction: The logical errors of visions adopted by dualistic positions are described and indicated, specifically in the context of cases that an individual reports suffering symptoms of a disease without a medically and verifiable pathological. According to this logic, the mental can suffer disease and affect the behavior. Method: A case of an adult man reporting different illnesses is exposed on this paper. The medical studies carried out do not confirm the presence of any pathology. This case is studied from a naturalistic and field perspective by applying the methodology of Contingential Analysis derived from interbehavioral psychology. The factors, circumstances and value criteria related to the presentation of the "illness behavior" of the psychological service user are identified. An intervention was designed and implemented to modify these aspects. Results: The intervention allowed the user to develop competencies to fulfill what was socially expected from him and to stop reporting the condition of diseases not medically demonstrable. Conclusions: The benefits of this naturalistic are indicated in ths work, compared to those that conceptualize this kind of cases as mental illnesses, whose interventions are oriented to the cure healing of the noncorporeal.